The representational and the presentational (Book Review); Foundational issues in artificial intelligence and cognitive science (Book Review) - Wheeler, Michael (British Journal of Psychology, 1998)
A review of two books on cognitive psychology is presented. The books are The Representational and the Presentational: An Essay on Cognition and the Study of Mind, by Benny Shannon, and Foundational Issues in Artificial Intelligence and Cognitive Science: Impasse and Solution, by Mark H. Brickhard and Loren Terveen. Both are critical books, in that they argue against certain orthodox ways of thinking, but they are also positive in that they suggest their own alternatives.